Fruit and vegetable sector: Agritrade Executive Brief Update 2013 - Technical Centre for Agricultural and Rural Cooperation; Eastern Africa Grain Council (Technical Centre for Agricultural and Rural Cooperation, 2013)
Given that around 37 ACP countries are involved in exporting fruits and vegetables to the EU, accounting for some 13% of EU imports, the development of fruit and vegetable policy in the EU has important implications for ACP countries. This Executive Brief presents the main trends of the EU fruit and vegetable sector in 2012-13, with special emphasis on elements such as the growing demand for sustainably produced horticultural produce; the new approach to controls on food and feed that will probably entail full cost recovery for inspections; the stricter application of SPS standards; the CAP reform; and the trade agreements with non-ACP third countries. Furthermore, the Brief analyses the challenges and opportunities for ACP countries, who have to put in place strategies for the diversification of markets but also for the distribution along the value chain of the costs for controls, inspections and certifications. Regional (or even pan-ACP) cooperation on a number of issues in the fruit and vegetable sector and the use of agricultural trade policy tools in support of the development of fruit and vegetable production for local markets are also discussed.